Experimental Investigation of Heat Transfer in Automotive Radiator Using CuO Nanofluids - Myo, Aye Aye; Latt, Aung Ko; Swe, War War Min; Soe, Aung Kyaw (The Indonesian Journal of Computer Science, 2024)
This paper focuses on the thermal analysis of an automotive radiator within the content of an engine cooling system. The cooling system plays a crucial role in regulating the temperature of a car’s engine. One of the essential components of the car’s cooling system is the cooling fluid. An efficient cooling system is vital in preventing engine overheating and ensuring the vehicle operates at its optimal performance level. A range of different approaches can be utilized to enhance heat transfer performance. To enhance heat transfer in radiator design, increasing the number of fins is a common approach, but this method has limitations, and current technology has already maximized its effectiveness. Nanofluid has been identified as a potential candidate for the automobile sector. Compared to water and water-ethylene glycol mixtures, the heat transfer coefficient of the nanofluid is significantly higher. This thesis investigates the performance of copper oxide nanofluids when mixed with a base fluid. In this study, the outlet temperature of copper oxide nanofluid is compared with ethylene glycol coolant in an automobile radiator. The nanofluid is tested at five different volume concentrations ranging from 0.1to0.5%.